Companion Planting in the school garden - Melissourgou, Effrosini; Kassari, Nefeli; Manoukaraki, Irene; Melissourgos, George; Awir, Amane; Vergaki, Irene; Dramitinos, Yiannis; Delilai, Ariadne; Yazi, Laith; Tsagliotis, Nektarios (Open Schools Journal for Open Science, 2019)
We would like to report and share our knowledge and practice from the school garden, regarding companion planting, that is “planting together with benefits”. Under our standard cultivating year-round approach, working on "seed to seed“ activities, we prepare our seed plants in the greenhouse, later to be transplanted to the garden raised beds in a companion planting mode, enhancing the benefits of companionship and biodiversity in action. We have tested many combinations over the last 12 years, as knowledge and practice is also passed on to us by older classmates and community members and we have found out that some combinations can actually help one or more of the companions flourish. Our vegetable crops are getting better and we are happy to have more quality products to share within the community.